Pathogenicity Of A Malaysian Fowl Adenovirus Isolate In Specific Pathogen Free Embryonated Chicken Eggs And Chicks - Yimer, Alemnesh Woldeyes (2009)

(untitled)
The pathogenic role of fowl adenoviruses (FAdVs) in disease outbreaks remained unestablished, as some findings showed that FAdVs are the primary infectious agents whilst others showed that these viruses can co-infect with other immunosuppressive agents to cause diseases. Thus, there is a need to establish the roles and characteristics of the virus in chicken to control and prevent the disease, especially by developing vaccine and introducing vaccination programme against the disease. The objective of the study was to isolate, identify and determine the pathogenicity of Malaysian isolate of FAdV in specific pathogen free (SPF) embryonated chicken eggs and chicks. Liver homogenate obtained from inclusion body hepatitis (IBH) field outbreaks in commercial broiler chicken was inoculated, passaged and titrated in SPF embryonated chicken eggs via chorioallantoic membrane (CAM) route and the FAdV was identified using electron microscopy. The virus inoculum with the titre of 1x 10 4.8 EID50/ 0.1 ml was then inoculated into 9-day-old SPF embryonated chicken eggs as well as 9-day-old SPF chicks. Control groups were included and remained non-inoculated. They were monitored for mortality and clinical signs. The eggs and chicks were either labeled for determination of the percentage of mortality or sacrificed at days 1, 3, 5, 7, 9, 11 and 12, and days 1, 3, 5, 7, 10, 14 and 21 post inoculations (pi), respectively. On necropsy, samples of liver, CAM, yolk sac, kidney, spleen, heart and bursa of Fabricius from the embryos were collected for histological examination, whilst the liver and CAM were also examined for ultrastructural changes. Samples of liver, spleen, gizzard, proventriculus, kidney, pancreas, duodenum and bursa of Fabricius of the chicks were also examined for histological changes, whilst samples of liver were examined for ultrastructural changes as well. The study showed 100% embryo mortality within 4 to 11 days pi of the virus in SPF embryonated chicken eggs. The gross and histological lesions of the embryo were confined in the liver at days 5, 7, 9 and 11 pi. Grossly the liver was pale with multi-focal areas of necrosis, fibrosis and hemorrhages. Histologically, moderate to severe congestion and hemorrhage, severe diffused degeneration and necrosis of the hepatocytes with intranuclear inclusion bodies (INIB), and infiltration of inflammatory cells were recorded. Hemorrhage, congestion, degeneration, necrosis and hyperplasia of the chorionic epithelium of CAM with INIB were observed at days 5, 7, 9 and 11 pi. Varying degree of congestion, hemorrhage, degeneration and necrosis were also observed in the yolk sac, kidney, spleen, heart and bursa of Fabricius. Numerous viral particles in the nucleus of hepatocytes were recorded at days 7, 9 and 11 pi under ultrastructural examination, whereas at 5 days pi fine granular and filamentous materials of inclusion bodies were observed. The INIB in the ectoderm were either as fine granular and filamentous structures or as large viral inclusions. Neither clinical signs nor mortality and gross lesions were observed in the chicks in both groups; the FAdV inoculated and control groups. However, histologically mild to moderate degeneration with focal areas of necrosis, presence of INIB and mild infiltration of inflammatory cells in the liver and mild degeneration and necrosis in the proventriculus and pancreas were observed at days 5 to 14 pi. Ultrastructurally, fibrillar, granular and filaments particles of INIB of the hepatocytes were recorded at days 5 to 14 pi. It was concluded that the FAdV of Malaysian isolate is highly pathogenic to SPF embryonated chicken eggs, but low pathogenic to the chicks. The embryonic liver is the best organ to be used for adaptation and passaging of the virus since severe lesions and numerous viral particles were observed in the liver, the target organ of the virus. The failure of the virus particles to develop in the hepatocytes could result in the failure of disease development in the FAdV infection in the chicks. It appears that the FAdV of Malaysian isolate has high potential to be used as a viral vector to produce recombinant vaccine against poultry diseases.